Allometric model for height estimation of Alnus acuminata Kunth in agroecological zones of the high Andean tropics - Bacca-Acosta, Pedro Pablo; Obando-Enriquez, Bayron Giovanny; Lerma-Lasso, Jose Libardo; Ortega-Cepeda, María Camila; Palacio, Manfred Ricardo; Zuluaga-Peláez, John Jairo (Revista de Ciencias Agrícolas, 2023)
The complexity in the management of field tools for recording dasometric information has led to the use of allometric equations that save time, work, and costs allowing the estimation of variables that are difficult to record, such as total height (TH). The objective of this research was to develop an allometric equation for the species Alnus acuminata in order to calculate TH from the diameter at breast height (DBH). At the Obonuco-AGROSAVIA Research Center in Pasto (Nariño), dasometric information was recorded for 75 months for 200 even-aged trees. Four models were evaluated: linear, polynomial, Mixed linear (random effect per tree age), and Mixed linear (random effect per tree). For the selection of the best model, the criteria were used with the lowest values ​​of Akaike (AIC) and Bayesian (BIC). The information was analyzed using the "Nonlinear Mixed-Effects Models" package, R software. The results revealed that A. acuminata had an 81% survival; the TH average was 7.4 ± 1.3 m; and the average DBH was 9.51 ± 2.23cm. The average annual increase of DBH was 1.5 cm year-1, and the TH was 1.18 m∙ per year-1. The mixed linear model confirmed the assumptions of normality, independence, and homogeneity of variances in addition of having good criteria in its predictive performance and efficiency through the equation TH=2.07+0.35*DBH+0.95*Age. This research contributes to the management of native species of the high tropics by designing an equation for the first vegetative growth phases of A. acuminata in high mountain agroecological zones.